Konsep Pemikiran Pendidikan Islam: Suatu Kajian Literatur (Tsamratul Fikri | Jurnal Studi Islam, 2022)
This study aims to elaborate on the concept of education and the concept of thought in Islamic education. This concept which is commonly studied in educational philosophy is seen as important considering that the study of educational thought is closely related to efforts to build the foundation of Islamic education. This study uses the literature review method, in which the researcher reviews books, journal articles, proceedings of relevant scientific activities, then analyzes them before writing them down in the text of this scientific article. The results of the study show that Islamic educational thinking is a fundamental field in the study of Islamic education. The thought of Islamic education is a place for the development of the foundations and foundations of Islamic education. Through the thought of Islamic education, every concept and theory of Islamic education is formulated and then developed in the realm of Islamic education practice. Islamic educational thinking is the starting point for the development of Islamic educational disciplines. Without the discipline of thought in Islamic education, it will be difficult to develop operational concepts and educational theories.